Properties of the viruses associated with disease complex of bell pepper - I.D. GARG2; S.M. PAUL KHURANA2, PREM N. SHARMA1, SUBHASH C. CHOWFLA1 (Indian Phytopathology, 2002)
Based on host range, symptomatology, transmission and electron microscopy, at least two different potyviruses and a cucumovirus associated with mosaic disease complex of bell pepper were characterized. Host range of these viruses was restricted. Symptoms induced in bell pepper included mosaic, mottling, vein banding, shoe-stringing, stunting and fruit deformities. All the isolates were sap as well as aphid transmissible (Myzus persicae). Particles of the isolates of polyviruses were f1exuous filaments measuring 741-785 x 12 nm, and those of the cucumovirus were isometric (27 nrn). Isolates of potyviruses induced cytoplasmic cylindrical inclusions and that of cucumovirus induced vesicles along the tonoplast. The cucumovirus isolate as serologically related to CMV -K; the isolates of potyviruses were not related to PVY.